Workstress Sebagai Variabel Mediasi Pengaruh Kompensasi dan Budaya Organisasi terhadap Kinerja Karyawan Industri Otomotif - Nugraha, Wisnujaya; Bangun, Wilson (SAFE-Network, 2025)
The automotive industry is one of the largest manufacturing commodities for export value in Indonesia. The automotive industry currently has two active generations of workers including generations Y and Z with different characteristics. Companies engaged in the automotive industry must be able to understand these characteristics so that performance remains in accordance with what the company wants. The purpose of this research is to ascertain and examine whether there influence of compensation and organizational culture with workstress as a mediating variable on employee performance, data collection was carried out by distributing questionnaires to 100 respondents with a purposive sampling method on employees in the automotive industry sector in Bandung with Smart-PLS software, and the results show that compensation and organizational culture with workstress as a mediating variable have a positive and significant effect on employee performance on generation Y and Z automotive industry employees in Bandung.